2008
DOI: 10.4069/kjwhn.2008.14.4.270
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on Parenting Stress, Guilt, Parenting Attitude, and Parenting Satisfaction Between Mothers with a Hemophilic Child and a Healthy Child

Abstract: 혈우아동과 일반아동 어머니의 양육스트레스, 죄책감, 양육태도 및 부모역할만족도 비교1) 경희대학교 간호과학대학 교수, 2) 제주한라대학 전임강사 3) 경희대학교 간호과학대학 연구교수 투고일: 2008. 8. 20 1차심사완료일: 2008. 10. 10 2차심사완료일: 2008. 11. 3 최종심사완료일: 2008. 12. 4 • Address reprint requests to : Ji, Eun-Sun(Corresponding Author) College of Nursing Science, Kyung Hee University 1, Hoegi-dong, Dongdaemun-gu, Seoul 130-701 Tel: 82-16-693-1154 Abstract Purpose: Although Hemophilia is a relatively rare hereditary disease, and is treatable with blood products, the parenting stress and guil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…This U-curve pattern is consistent with existing literature on migrant distress (Furnham and Bochner 1989). Among female North Korean migrants, there is a noted trend of increasing depressive symptoms with longer stays in South Korea (Kim 2012). Most research, however, is cross-sectional, highlighting a need for more longitudinal studies.…”
Section: Literature Review On the Health Status Of Female North Korea...supporting
confidence: 87%
“…This U-curve pattern is consistent with existing literature on migrant distress (Furnham and Bochner 1989). Among female North Korean migrants, there is a noted trend of increasing depressive symptoms with longer stays in South Korea (Kim 2012). Most research, however, is cross-sectional, highlighting a need for more longitudinal studies.…”
Section: Literature Review On the Health Status Of Female North Korea...supporting
confidence: 87%
“…Particularly in South Korea, where rates of pediatric cancer survival are high (Korea Central Cancer Registry, National Cancer Center, 2017), how mothers choose to parent their child with cancer can be unique. Kim, Kang, Cho, Song, and Ji (2008) found that mothers with a hemophilic child reported higher levels of parenting stress and guilt, more negative parenting attitudes, and lower levels of parenting satisfaction than those with a healthy child. A few studies examined parental rearing behaviors on health-related quality of life (Kim, Chung, & Lee, 2015) and school adjustment (Lee & Kim, 2017) among South Korean adolescents with leukemia.…”
Section: Rationalementioning
confidence: 91%
“…According to Wiedebusch et al [3], rearing hemophilic children makes a moderate impact on the parents in terms of quality of life. Parenting stress is higher in the mothers of hemophilic children compared to the mothers of healthy children [8]. In addition, stress of the parents is correlated with increase in bleeding frequency of the hemophilic children while psychosocial support decreases need of transfusion in hemophilic patients [9,10].…”
Section: Introductionmentioning
confidence: 98%